Advancing Pharmaceutical Reliability: Innovations in Stability-Indicating Assay Methods - Reddy, Daram Sushma; Bannimath, Gurupadayya; Kondru, Sruthi; Manepally, Anupama; Kaveti, Manognya; Jain, Rupshee (Indian Journal of Pharmaceutical Education and Research)
The design and development of Stability-Indicating Assay Methods (SIAMs) are critical in the pharmaceutical industry to ensure the safety and efficacy of drug products throughout their shelf-life. These methods are specifically tailored to detect and quantify the Active Pharmaceutical Ingredient (API) and any potential degradation products under various stress conditions. Advanced analytical techniques such as HPLC, GC, and MS play pivotal roles in these developments. Ongoing advancements in technology and methodology, including the integration of machine learning and high-throughput systems, are not just trends but also the future of SIAMs. They forecast a future where SIAMs are more robust, efficient, and environmentally sustainable, revolutionizing how we ensure drug product quality. This paper explores current practices and future perspectives in the field, highlighting the importance of regulatory compliance and the impact of these technological innovations on method development. This review is intended to analyze innovations in stability-Indicating Assay Methods in the Pharmaceutical Lifecycle. Stability-indicating assays are crucial for determining the stability of pharmaceutical compounds and ensuring their safety and efficacy over time via different analytical methods, such as High-Performance Liquid Chromatography (HPLC), Gas Chromatography (GC-MS), and Ultra-Pressure Liquid Chromatography (UPLC). Validation parameters: Specificity, precision, linearity, robustness, LOD, and LOQ and sensitivity. Validation of these parameters ensures that the SIAM is fit for its intended purpose and can reliably measure the stability of pharmaceutical products, helping maintain their quality and efficacy throughout their shelf-life. The field of Stability Indicator Assay Methods (SIAMs) is undergoing significant evolution due to rapid technological advancements and increasing regulatory demands.
Keywords: Analytical techniques; GC; HPLC; MS; Pharmaceutical stability; Regulatory Compliance; SIAMs; Stability Indicator Assay methods.